The importance of educational research and the challenges it from the perspective of educational supervisors - Albalawi, Fahad Olayan (Journal of Educational and Psychological Sciences, 2022)
The current research aims to identify: the importance of educational research and the challenges it faces from the perspective of educational supervisors in the Kingdom of Saudi Arabia, the extent to which educational supervisors practice educational research in Saudi society, as well as to provide suggested visions for the development of educational research in Saudi universities. The researcher adapted the study tool (the questionnaire) from Alsharify's 2014 study. This research was conducted on educational supervisors (boys) in Tabuk education's supervision department. The research sample was chosen at random, with a sample size of (36) supervisors, and the research was carried out during the second semester of the year 1442 AH. The research found several important findings, the most important of which are: educational supervisors use educational research mechanisms to a large extent, and educational supervisors face difficulties and challenges while conducting educational research. The researcher recommended that efforts be made to increase the financial and moral incentives provided to the researcher, as well as more training courses to develop the capabilities and skills of supervisors, and working to increase the number of libraries used by the researcher within the city.
Keywords: Educational research; educational supervisor; educational supervision; training courses; skills of supervisors; financial incentives